Meta-metallation of N,N-dimethylaniline: Contrasting direct sodium-mediated zincation with indirect sodiation-dialkylzinc co-complexation - Armstrong, David R.; Balloch, Liam; Hevia, Eva; Kennedy, Alan R.; Mulvey, Robert E.; O'Hara, Charles T.; Robertson, Stuart D. (Beilstein Journal of Organic Chemistry, 2011)
Previously we reported that direct zincation of N,N-dimethylaniline by the mixed-metal zincate reagent 1 ((TMEDA)Na(TMP)(t-Bu)Zn(t-Bu)) surprisingly led to meta-metallation (zincation) of the aniline, as manifested in the crystalline complex 2 ((TMEDA)Na(TMP)(m-C6H4-NMe2)Zn(t-Bu)), and that iodination of these isolated crystals produced the meta-isomer N,N-dimethyl-3-iodoaniline quantitatively. Completing the study here we find that treating the reaction solution with iodine produces a 72% conversion and results in a mixture of regioisomers of N,N-dimethyliodoaniline, with the meta-isomer still the major product (ortho:meta:para ratio, 6:73:21), as determined by NMR. In contrast to this bimetallic method, sodiation of N,N-dimethylaniline with n-BuNa produced the dimeric, ortho-sodiated complex 3 (((TMEDA)Na(o-C6H4-NMe2))2), as characterised by X-ray crystallography and NMR. No regioisomers were observed in the reaction solution. Introducing t-Bu2Zn to this reaction solution afforded a cocrystalline product in the solid-state, composed of the bis-anilide 4 ((TMEDA)Na(o-C6H4-NMe2)2Zn(t-Bu)) and the Me2N–C cleavage product 5 ({(TMEDA)2Na}+{(t-Bu2Zn)2(µ-NMe2)}−), which was characterised by X-ray crystallography. NMR studies of the reaction mixture that produces 4 and 5 revealed one additional species, but the mixture as a whole contained only ortho-species and a trace amount of para-species as established by iodine quenching. In an indirect variation of the bimetallic reaction, TMP(H) was added at room temperature to the reaction mixture that afforded 4 and 5. This gave the crystalline product 6 ((TMEDA)Na(TMP)(o-C6H4-NMe2)Zn(t-Bu)), the ortho-isomer of the meta-complex 2, as determined from X-ray crystallographic and NMR data. Monitoring the regioselectivity of the reaction by iodination revealed a 16.6:1.6:1.0 ortho:meta:para ratio. Interestingly, when the TMP(H) containing solution was heated under reflux for 18 hours more meta-isomer was produced (corresponding ratio 3.7:4.2:1.0). It is likely that this change has its origin in a retro reaction that produces the original base 1 as an intermediate. Theoretical calculations at the DFT level using the B3LYP method and the 6-311G** basis set were used to probe the energetics of both monometallic and bimetallic systems. In accord with the experimental results, it was found that ortho-metallation was favoured by sodiation; whereas meta- (closely followed by para-) metallation was favoured by direct sodium-mediated zincation.
Keywords: alkali metal; crystal structure; isomerisation; metallation; zincation